Pemberdayaan Gen-Z Sebagai Gerakan Masyarakat Sadar Wisata (Penerapan di Lingkungan Universitas Widya Mataram Yogyakarta) - Ningrum, Dyaloka Puspita (Jurnal Ilmiah Padma Sri Kreshna, 2025)
This Community Service Activity aims to empower Gen-Z in the Widya Mataram University Yogyakarta Campus environment as a tourism-aware society, especially through active participation in Instagram social media. The involvement of the beneficiary group is expected to take a real role in boosting tourism potential which in the future can even be used as an increasingly prominent tourist destination, because the tourism resources in the Special Region of Yogyakarta are increasingly progressive over time. The activity method is carried out in stages by means of: lectures, discussions-questions and answers, and trials / practices of creating digital content as promotional materials as well as branding on Instagram social media. The results of the activity were carried out smoothly in January 2025 which was attended by 25 participants. An educational and persuasive approach is an effort that is strengthened by the facilitator team regarding the phenomenon of the high culture of searching and sharing in the digital space, so that the beneficiary group is directed to become tourism development agents as the concept of creative people in planning to implementation and development. The products created by the beneficiary group are in the form of fun and informative tourism content on Instagram social media, especially regarding activities in: local community culture, iconic artificial attractions, or various culinary tourism attractions.